Disabling Fields, Enabling Capital: Mothers with Disabilities and the Concerted Cultivation Habitus - Frederick, Angela (Disability Studies Quarterly, 2018)
This article examines the experiences of mothers with disabilities who engage in concerted cultivation, a parenting style commonly practiced in middle-class communities. The author explores these mothers' experiences in the "fields" of their children's schools and organized extracurricular activities. Findings illuminate how ruptures in these mothers' middle - class habitus occur as they confront accessibility barriers and social exclusion while engaging in concerted cultivation. These mothers are found to simultaneously deploy class-based resources to overcome these barriers. This analysis lays bare the ways in which the concerted cultivation habitus presumes a nondisabled identity.